Electrochemical reduction of the mycotoxin citrinin at bare and modified with multi-walled carbon nanotubes glassy carbon electrodes in a non-aqueous reaction medium - Zachetti, Vanessa Gimena Lourdes (2012)
The electrochemical reduction mechanism of citrinin in acetonitrile + 0.1 mol L-1 (C4H9)4NClO4 at both bare and modified with multi-walled carbon nanotubes glassy carbon electrodes has been investigated for the first time, by cyclic voltammetry and controlled potential electrolysis. Results allowed to infer a complex electro-reduction mechanism with chemical and electrochemical steps coupled to the initial electron transfer reaction. Citrinin shows a single cathodic voltammetric peak which corresponds, at least, to two electron reductions steps and two homogeneous chemical reactions, conforming to an ECEC self-protonation mechanism. The chemical reactions stems intermolecular proton transfers from the substrate to its basic reduction intermediates, featuring a self-protonation mechanism. Kinetics analysis by simulation procedures of voltammetric results have permitted to fully characterized the mechanism of citrinin heterogeneous reduction.